Episodic hydrothermal activities impact on organic matter enrichment in the post-collision rift basin of Permian Lucaogou Formation, southern Junggar Basin, NW China - Jiao, Yue; Wu, Chaodong; Zhou, Tianqi; Wang, Jialin (Frontiers in Earth Science, 2023)
The factors controlling the organic matter accumulation in the organic-rich shale of the Lucaogou Formation in the southern Junggar Basin, remain controversial. To more explicitly reveal the hydrothermal events and its mechanism on the organic matter enrichment, we performed mineralogy and geochemistry methods on dolomite and black shale samples from Well FK-1 in Fukang Sag. The high (Fe + Mn)/Ti ratios, the enrichment of Ca, Mg, Fe, Mn, and REY, and multiple hydrothermal minerals (e.g., ankerite, dolomite, zeolite, authigenic albite, and microcline) suggest five episodes of hydrothermal events. In addition, the low-to-high-varied Sr/Ba, V/(V + Ni) (Al + Fe)/(Ca + Mg), and Sr/Cu ratios, as well as the dolomite formation all well indicate a brackish-saline, suboxic-anoxic, shallow to deep water condition under a warm-humid to hot-arid climate with rhythmic sedimentation. The fluctuated total organic carbon content (up to 12.16 wt%) suggest the periodic organic matter accumulation. Three patterns of organic matter enrichment occurred during the rift-drift transition of the southern Junggar Basin, productivity and preservation played distinguishing roles in different intervals. Productivity periodically fluctuated because of the episodic hydrothermal events and warm-humid climate changes. Preservation was triggered by the saline, anoxic, and well-stratified water setting under the relatively hot-arid climate, which became progressively favorable in the gradually stabilized basin.